Analysis of Geographically Weighted Regression (GWR) on Factors Affecting Zakat Funds in South Sulawesi Province - Nur, Awal; Sofyan, A. Syathir; Sirajuddin, Sirajuddin; Parakkasi, Idris; Wulandari, Gesia Afifah Ayu (EQUILIBRIUM, 2026)
This study examines the factors influencing zakat funds in South Sulawesi Province using the Geographically Weighted Regression (GWR) method. The zakat funds in this study focus on zakat collections in 2022 across 24 regencies and cities in South Sulawesi Province. A gap in the existing literature was identified in previous studies, which generally relied on global regression and did not account for spatial variation across regions. This study utilized secondary data obtained from the Central Statistics Agency (BPS) and the National Zakat Agency (BAZNAS), with three independent variables: Gross Regional Domestic Product (GRDP), the Human Development Index (HDI), and the Muslim population. The GWR method was applied to capture local parameter variations that may differ across regions. The results indicate that the GWR model performs better than the multiple linear regression model, as evidenced by lower AIC values and smaller residuals. The Muslim population variable has a positive and significant effect on zakat funds, whereas the GRDP and HDI variables do not show significant effects. These results indicate that demographic factors, particularly the Muslim population, are the dominant factors influencing zakat funds in South Sulawesi Province. Therefore, region-based zakat management must take into account local social, economic, and demographic characteristics to ensure that zakat collection strategies are implemented more effectively. These findings contribute to the development of data-driven zakat policies that account for regional considerations in Indonesia.